An electrochemical immunosensing system on patterned electrodes for immunoglobulin E detection. Issue 35 (27th August 2019) - Oh, Seung Jun; Ahn, Jun Ki; Park, Hun; Song, Yesol; Kwon, Seong Jung; Shin, Hang-Beum
Abstract : We present an electrochemical biosensing platform which enables immunoglobulin E (IgE) detection from eight independent biological samples. The performance of the electrochemical immunosensor was comparable to the conventional optical assay. Abstract : We present an electrochemical biosensing platform which enables immunoglobulin E (IgE) detection from eight independent biological samples. The performance of the electrochemical immunosensor was comparable to the conventional optical assay. This biosensor would be a powerful tool for multiple IgE diagnoses, taking advantage of outstanding electrochemical assays.